Ethnic Differences in Assisted Reproductive Technologies Outcomes - Spitzer, Trimble; Fujimoto, Victor Y. (Seminars in Reproductive Medicine, 2013)
Disparities in assisted reproductive technologies (ARTs) outcomes have been identified among ethnic minorities when compared with their Caucasian counterparts. Minority ethnicity has been shown to be an independent predictor of lower clinical pregnancy and live birth rates in many studies. In this article, we seek to summarize the most recent literature on ethnic difference reported within ART outcomes. We will discuss potential reasons behind these disparities and further explore independent predictors and associations between ethnicity and ART success.
Keywords: ethnicity; ART; IVF; ethnic disparity